2006
DOI: 10.1111/j.1365-2486.2006.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Conifer stem growth at the altitudinal treeline in response to four years of CO2 enrichment

Abstract: Northern latitude and upper altitude climatic treelines have received increasing attention given their potential sensitivity to atmospheric and climate change. While greater radial stem growth at treeline sites in recent decades has been attributed largely to increasing temperature, rising atmospheric CO 2 concentration may also be contributing to this growth stimulation. Tree ring increments of mature Larix decidua and Pinus uncinata were measured over 4 years in a free air CO 2 enrichment experiment at treel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 86 publications
6
65
1
1
Order By: Relevance
“…To date, existing experiments have demonstrated that rising atmospheric [CO 2 ] results in increases in net primary production (NPP) and C storage in forest vegetation, e.g. (Calfapietra et al, 2003;DeLucia et al, 1999;Gielen et al, 2005;Hamilton et al, 2002;Handa et al, 2006;Karnosky et al, 2003;Liberloo et al, 2009;Norby et al, 2002). Norby et al (2005) analyzed the response of NPP (g C m −2 y −1 ) to elevated [CO 2 ] in four forest FACE experiments and calculated the following regression NPP elev = 1.18×NPP amb + 55.4 (r 2 = 0.97).…”
Section: Introductionmentioning
confidence: 99%
“…To date, existing experiments have demonstrated that rising atmospheric [CO 2 ] results in increases in net primary production (NPP) and C storage in forest vegetation, e.g. (Calfapietra et al, 2003;DeLucia et al, 1999;Gielen et al, 2005;Hamilton et al, 2002;Handa et al, 2006;Karnosky et al, 2003;Liberloo et al, 2009;Norby et al, 2002). Norby et al (2005) analyzed the response of NPP (g C m −2 y −1 ) to elevated [CO 2 ] in four forest FACE experiments and calculated the following regression NPP elev = 1.18×NPP amb + 55.4 (r 2 = 0.97).…”
Section: Introductionmentioning
confidence: 99%
“…Climate envelope models and tree ring analyses imply suitable habitat is largely defined by climate variables (Littell et al 2010;Mckenzie et al 2003;Nitschke and Innes 2008). Additionally, growth and mortality of conifers are known to be sensitive to temperature, soil moisture (likely to decrease with warmer temperatures), and CO 2 (Fritts 1974;Gregg et al 2003;Handa et al 2006;Holman and Peterson 2006), particularly at seedling stages (Yin et al 2007). Recent studies demonstrate that tree mortality is increasing in western North America (van Mantgem et al 2009), raising the possibility of a sudden loss of adult trees.…”
mentioning
confidence: 99%
“…Some works conducted at some trees grown in Swiss Alps (2,180 m a.s.l.) have shown that the CO 2 -induced increase in photosynthesis has been maintained, and the initial increase in growth rate has also been sustained in Larix deciduas (Handa et al 2006;Dawes et al 2013;Streit et al 2014). Downward adjustment of photosynthetic capacity by -26 % on average under long-term exposure to elevated CO 2 has been observed in Swiss Alps (2,440 m a.s.l., Inauen et al 2012).…”
Section: Introductionmentioning
confidence: 85%
“…Our research found greater increases of NSC in HE population than in LE population. Excess C accumulates as NSC in leaves under elevated CO 2 (Handa et al 2006;Onoda et al 2009;Zhao et al 2011), but the level of increases in NSC concentrations depends on species and conditions (Stitt and Krapp 1999). A larger change in NSC detected in HE population than in LE population under elevated CO 2 suggests a large sink capacity in HE population (Handa et al 2006;Wu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation